Analysis of lateral ankle sprain injury in badminton with a model-based image-matching forensic video analysis method - Wang, Y.; Zhang, J.; Fong, D. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to examine the kinematics of an acute lateral ankle sprain sustained during a televised badminton match. A clip of an acute lateral ankle injury sustained during a match was edited and imported into Poser 4 and Poser Pro Pack to match the badminton court ground line and the player's skeletal model. Internal rotation rose with time and peaked at 57° at 0.28s, plantarflexion peaked at 22° at 0.08s and subsequently decreased, and inversion peaked at 92° at 0.2s. The maximal plantarflexion, internal rotation, and angular velocity of internal rotation were 492°/s, 921°/s, and 969°/s, respectively. After the strike, the ankle injury developed as a result of ankle inversion and internal rotation motions. To reduce ankle injuries in badminton, players should maintain a regulated landing posture while adjusting for environmental conditions and increase their strength and conditioning training on landing skills.